2012
DOI: 10.1097/aog.0b013e318234d97c
|View full text |Cite
|
Sign up to set email alerts
|

Progestin Intrauterine Device in an Adolescent With Grade 2 Endometrial Cancer

Abstract: Background The treatment of endometrial cancer in young women who desire future fertility poses several challenges. Oral progestin and progestin-releasing intrauterine devices (IUDs) have been shown to result in regression of endometrial hyperplasia and grade 1 endometrioid endometrial carcinoma. However, limited data are available on the use of these methods in women with grade 2 disease. Case An 18 year-old nulliparous woman was diagnosed with a grade 2 endometrial adenocarcinoma. She desired future fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 11 publications
1
38
0
Order By: Relevance
“…Sometimes, however, patients with superficial myometrial invasion and/orgrade 2-3 disease may want to preserve their fertility. Only a few studies have reported the outcomes of fertility-sparing treatment in patients with stage IA, grade 2-3 disease without myometrial invasion as a part of their wider analyses (Table 2) [19, 51,[103][104][105][106][107]. Recently, Park et al [12] reported the oncologic and reproductive outcomes in a cohort of endometrial cancer patients with superficial myometrial invasion and/orgrade 2-3 disease.…”
Section: Progestin Therapy For More Advanced Diseasementioning
confidence: 99%
“…Sometimes, however, patients with superficial myometrial invasion and/orgrade 2-3 disease may want to preserve their fertility. Only a few studies have reported the outcomes of fertility-sparing treatment in patients with stage IA, grade 2-3 disease without myometrial invasion as a part of their wider analyses (Table 2) [19, 51,[103][104][105][106][107]. Recently, Park et al [12] reported the oncologic and reproductive outcomes in a cohort of endometrial cancer patients with superficial myometrial invasion and/orgrade 2-3 disease.…”
Section: Progestin Therapy For More Advanced Diseasementioning
confidence: 99%
“…For patients who are contraindicated to receive oral progestin or those with complaints of systemic side effects, LNG-IUS, which works locally in the endometrium, can be used. Recent studies have reported that combination treatment shows better results than single LNG-IUS treatment [89101112131819]. In particular, Kim et al [28] conducted a prospective observational study where MPA 500 mg/day and LNG-IUS were used in 16 patients with early-stage EC and reported that complete remission without any particular side effect was observed in 14 of 16 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, studies should investigate other diagnostic tools that can substitute for D&C, with less invasiveness and less risk of injuring the endometrium. Several studies investigated the accuracy of EM aspiration biopsy conducted without LNG-IUS removal after treating EC with LNG-IUS [910111213181920]. However, no study has evaluated the accuracy of EM aspiration biopsy after LNG-IUS removal in EC patients treated with high-dose progesterone and LNG-IUS therapy, and whether it can substitute for D&C. This study aimed to compare the accuracy of EM aspiration biopsy conducted after LNG-IUS removal and D&C biopsy in order to evaluate the treatment responses of patients with early EC conservatively treated with high-dose oral progestin and LNG-IUS, and its usefulness.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative for younger women wishing to preserve fertility, progestin-containing intrauterine devices (IUDs) have been used with reasonable safety and efficacy (21, 22), though this has predominantly been performed in patients with grade 1 disease. However, one case of grade 2 has been reported to be successfully treated (21). …”
Section: Surgical Procedures For Endometrial Cancermentioning
confidence: 99%